Analysis of digital governance transition in South Korea: Focusing on the leadership of the president for government innovation - Choong-sik Chung; Hanbyul Choi; Youngmin Cho (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This research intends to draw implications for digital governance establishment by analyzing how the president's leadership has worked in the digital government innovation promoted in South Korea over the past 30 years. This research examines the process of digital government development in South Korea from the 1990s onwards, chronologically and in the order of presidential administrations. The analysis proceeds from the following three perspectives: the political characteristics of digital government, the presidents' leadership on government innovation through digital government process, and the composition of a strong cross and joint governmental promotion system. The implementation of digital government is not simply about a computerized government. Driving digital government means the overall transformation of government. From this point of view, to successfully implement digital governance, we must approach it from a highly political perspective. The implementation of digital government in South Korea has been continuously pursued as a national agenda. Since South Korea has a well-established high-speed information and communication infrastructure, e-Government and digital government innovation have been promoted as national agendas regardless of regime change. However, in this process, the president's leadership determined the success or failure of digital government innovation. Therefore, the most important success factor for digital government innovation is securing policy sustainability regardless of administration change.
Keywords: 650; digital governance; digital government; digital transformation; e-Government; government innovation; information and communication technology (ICT)